Show that :
(i) tan 48° tan 23° tan 42° tan 67° = 1
(ii) cos 38° cos 52° - sin 38° sin 52° = 0
Answers
Answered by
1
Explanation:
1) tan48 .tan23.tan42.tan67=1
can be written as :-
tan48.tan42.tan23.tan67=1
we know that tan
so, tan48.cot48.tan23.cot23=1
* tan A × cot A=1*
so
1=1
LHS=RHS
Answered by
1
Answer:
(i) Taking LHS
tan 48° tan 42° tan 23° tan 67°
= tan 48° tan(90°- 48°) tan 23° tan(90° -23°)
= tan 48° cot 48° tan 23° cot 23°
= (tan 48⁰ x 1/tan 48°) x (tan 23° x 1/tan 23°)
= 1 X 1
= 1
= RHS
-
(ii) LHS
= cos 38° cos 52°sin 38°. sin 52°
= cos (90°-52°). cos 52°-sin (90°52°). sin 52°
= sin 52°. cos 52° cos 52°. sin 52°
= 0 = RHS
Similar questions